2000
DOI: 10.1161/01.atv.20.12.2573
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of Angiopoietin-1 and Vascular Endothelial Growth Factor Enhances Collateral Vascularization

Abstract: Abstract-Using growth factors to induce vasculogenesis is a promising approach in the treatment of ischemic legs and myocardium. Because the vasculogenesis requires a cascade of growth factors, their receptors, and intracellular signals, such therapies may require the application of more than a single growth factor. We examined the effect of 2 endothelial cell-specific growth factors, angiopoietin-1 (Ang1) and vascular endothelial growth factor (VEGF), on primary cultured porcine coronary artery endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
152
3
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(167 citation statements)
references
References 37 publications
(29 reference statements)
11
152
3
1
Order By: Relevance
“…In a transgenic mouse model with increased co-expression of Ang-1 and VEGF, angiogenesis was also increased (Thurston et al, 1999). This phenomenon of an enhanced vasculogenesis by combining Ang-1 with VEGF was also demonstrated by Chae et al (2000). Using a rabbit ischaemic hind-limb model, they demonstrated that a combination of Ang-1 and VEGF gene delivery resulted in the formation of larger blood vessels, increased blood flow and higher capillary density than was seen when either factor was delivered alone.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a transgenic mouse model with increased co-expression of Ang-1 and VEGF, angiogenesis was also increased (Thurston et al, 1999). This phenomenon of an enhanced vasculogenesis by combining Ang-1 with VEGF was also demonstrated by Chae et al (2000). Using a rabbit ischaemic hind-limb model, they demonstrated that a combination of Ang-1 and VEGF gene delivery resulted in the formation of larger blood vessels, increased blood flow and higher capillary density than was seen when either factor was delivered alone.…”
Section: Discussionmentioning
confidence: 72%
“…The effects of the angiopoietins on angiogenesis, tumour growth and vascular permeability remain controversial (Suri et al, 1998;Chae et al, 2000;Hayes et al, 2000;Ahmad et al, 2001;Shim et al, 2001). Some studies suggest that Ang-1 may be pro-angiogenic (Suri et al, 1998;Hansbury et al, 2001;Shim et al, 2001), whereas others have shown that Ang-1 inhibits angiogenesis, tumour growth and vascular permeability (Chae et al, 2000;Hayes et al, 2000;Thurston et al, 2000;Ahmad et al, 2001;Tian et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since Ang1 is not a mitogen, the increased vascular branching may arise from reinforcement of VEGF-induced angiogenesis. Indeed, Ang1 has been shown to synergise with VEGF to enhance angiogenesis in the rat aorta model [33] and increase vessel density in the corneal implant assay [34] and several other in vivo assays [35][36][37][38]. While overexpression of VEGF alone gives rise to increased vascular branching, the vessels induced by VEGF are leaky [32].…”
Section: Angiopoietins and Tie2mentioning
confidence: 99%
“…It is thought that the antagonism of Ang1-induced vascular stability by Ang2 leads to dissociation of the mural cell coating to initiate angiogenesis; the ratio of Ang1 to Ang2 is likely to be a critical determinant in this process. In the presence of VEGF, endothelial cells can proliferate, migrate, and form tubules, and in some cases this may act in synergy with Ang1 that is present [32,36,37]. It is tantalizing to suggest that the expression of Tie2 by mural cells and their precursors, and the ability of VEGF to upregulate Tie2 on these cells, renders them responsive to Ang1-mediated migration, leading to investiture of the endothelial tubule with mural cells.…”
Section: Inhibition Of Tumor Growth B Ang1 Overexpressionmentioning
confidence: 99%